PENGARUH MINAT KEWIRAUSAHAAN TERHADAP ENTREPRENEURIAL INTENTION MAHASISWA PENDIDIKAN EKONOMI IKIP BUDI UTOMO MALANG - Novi Eko Prasetyo; Putri Vina Sefaverdiana; Titik Purwati (Paradigma: Jurnal Filsafat, Sains, Teknologi, dan Sosial Budaya, 2017)
Entrepreneurs are one of the important figures in improving economic growth in a country, the number of young entrepreneurs in Indonesia is still not ideal. It is necessary for the participation of certain institutions such as Institutions to take an active role in increasing the number of new young entrepreneurs. IKIP Budi Utomo is one of the institutions that actively participates in increasing the number of young entrepreneurs by facilitating students to follow programs that encourage students’ intention to become entrepreneurs. This study aims to examine the influence of entrepreneurial interest on entrepreneurial intention of economic education students IKIP Budi Utomo Malang. The sample of this research are 48 students of economic education. The analysis tool used in this research is simple regression. From the results of the analysis can be concluded that entrepreneurial interest positive effect on entrepreneurial intention this is because students in doing business dominated by internal factors and external factors.